GOOGLE: a reflection of culture, leader, and management - Sang Kim Tran Tran (International Journal of Corporate Social Responsibility (JCSR), 2017)
This paper provides a viewpoint of the culture and subcultures at Google Inc., which is a famous global company, and has a huge engineering staff and many talented leaders. Through its history of development, it has had positive impacts on society; however; there have been management challenges. The Board of Directors (BoDs) developed and implemented a way to measure the abilities of their managers, which helped to identify problems. This paper will analyze the case study of Harvard Business Review, Oxygen Project, and clarify the management problem in Google's organization. It will also compare Google with Zappos, a much smaller organization, and present how the BoDs of Zappos assesses its culture and subcultures. In this paper, we will recommend eight important points to building an organizational culture that is positive for stable growth of a company. We believe that much of what be learned could be useful to other business leaders, regardless of company scale.
Keywords: 650; Culture; Subculture; Organizational culture; Management style; Oxygen project; Google